2019
DOI: 10.1107/s2056989019012490
|View full text |Cite
|
Sign up to set email alerts
|

(N,N-Diisopropyldithiocarbamato)triphenyltin(IV): crystal structure, Hirshfeld surface analysis and computational study

Abstract: The crystal and molecular structures of the title triorganotin dithiocarbamate, [Sn(C6H5)3(C7H14NS2)], are described. The molecular geometry about the metal atom is highly distorted being based on a C3S tetrahedron as the dithiocarbamate ligand is asymmetrically chelating to the tin centre. The close approach of the second thione-S atom [Sn...S = 2.9264 (4) Å] is largely responsible for the distortion. The molecular packing is almost devoid of directional interactions with only weak phenyl-C—H...C(phenyl) inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…A study by Balas et al [18] similarly showed cell cycle inhibition occurring in the S phase when leiomyosarcoma cells were treated with triphenyltin (IV) compounds. In addition, triphenyltin (IV) compounds have a greater toxic effect than diphenyltin (IV) compounds on human colorectal cancer, according to a study by Haezam et al [19]. Adeyemi et al [20] stated that the functional groups linked to tin atoms had in vitro toxic effects on the examined cells.…”
Section: Resultsmentioning
confidence: 99%
“…A study by Balas et al [18] similarly showed cell cycle inhibition occurring in the S phase when leiomyosarcoma cells were treated with triphenyltin (IV) compounds. In addition, triphenyltin (IV) compounds have a greater toxic effect than diphenyltin (IV) compounds on human colorectal cancer, according to a study by Haezam et al [19]. Adeyemi et al [20] stated that the functional groups linked to tin atoms had in vitro toxic effects on the examined cells.…”
Section: Resultsmentioning
confidence: 99%
“…The aforementioned report on tin diallyldithiocarbamate compounds (Adeyemi et al, 2019) also presented the first crystal-structure determinations for tin compounds of diallyldithiocarbamate. In a continuation of recent structural studies in this area (Mohamad et al, 2017(Mohamad et al, , 2018aHaezam et al, 2019), herein, two organotin compounds of diallyldithiocarbamate, (C 6 H 5 ) 3 Sn[S 2 CN(CH 2 C(H) CH 2 ) 2 ], (I), and (C 6 H 5 ) 2 Sn[S 2 CN(CH 2 C(H) CH 2 ) 2 ] 2 , (II), have been synth-esized and studied by X-ray crystallography. In addition, the supramolecular associations in their crystals have been evaluated by Hirshfeld surface analyses and computational chemistry.…”
Section: Chemical Contextmentioning
confidence: 85%
“…Seven organotin(IV) dithiocarbamate compounds, which are diphenyltin(IV) diisopropyl dithiocarbamate (ODTC 1), diphenyltin(IV) diallyl dithiocarbamate (ODTC 2), triphenyltin(IV) diisopropyl dithiocarbamate (ODTC 3), triphenyltin(IV) diallyl dithiocarbamate (ODTC 4), triphenyltin(IV) diethyl dithiocarbamate (ODTC 5), dimethyltin(IV) diisopropyl dithiocarbamate (ODTC 6) and dimethyltin(IV) diethyl dithiocarbamate (ODTC 7) were synthesized and characterized by our team (Haezam et al) [22,47,48] at the School of Chemical Sciences and Food Technology, Faculty of Science and Technology, Universiti Kebangsaan Malaysia, Bangi, Malaysia.…”
Section: Compoundsmentioning
confidence: 99%